2023
DOI: 10.1002/hon.3208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MAPK activation via mutations in NRAS, KRAS and BRAF on clinical outcome in newly diagnosed multiple myeloma

Camille Perroud,
Dario Thurian,
Martin Andres
et al.

Abstract: Until now, next generation sequencing (NGS) data has not been incorporated into any prognostic stratification of multiple myeloma (MM) and no therapeutic considerations are based upon it. In this work, we correlated NGS data with (1) therapy response and survival parameters in newly diagnosed multiple myeloma, treated by VRd * and (2) MM disease stage: newly diagnosed multiple myeloma (ndMM) versus relapsed and/or refractory (relapsed/refractory multiple myeloma). We analyzed 126 patients, with ndMM and relaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 95 publications
0
0
0
Order By: Relevance
“…Myeloma cells proliferate, leading to the formation of tumors, infiltration of the bone marrow, and subsequent depletion of red and white blood cells. Genetic anomalies in oncogenes such as CMYC , NRAS , and KRAS may affect the growth of plasma cells; however, the specific cause remains unclear [ 69 , 70 , 71 ]. Multiple myeloma stem cells, like cancer stem cells or leukemic stem cells, are functionally and phenotypically heterogeneous and induce resistance to chemotherapy and radiation therapy [ 72 ].…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…Myeloma cells proliferate, leading to the formation of tumors, infiltration of the bone marrow, and subsequent depletion of red and white blood cells. Genetic anomalies in oncogenes such as CMYC , NRAS , and KRAS may affect the growth of plasma cells; however, the specific cause remains unclear [ 69 , 70 , 71 ]. Multiple myeloma stem cells, like cancer stem cells or leukemic stem cells, are functionally and phenotypically heterogeneous and induce resistance to chemotherapy and radiation therapy [ 72 ].…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…Mutations in the PSMB5 gene are implicated in resistance to proteasome inhibitors (PI, e.g., bortezomib), while mutations in CRBN and genes of the Cereblon pathway are associated with resistance to treatment with immunomodulatory agents (IMiDs) [36,37]. Only very recently, Perroud et al showed that mutations in the MAPK pathway are associated with unfavorable outcomes in patients treated with PI/IMiD combinations [15]. Furthermore, it has been reported that mutations in TP53, ATM, ATR, and CCND1 confer to an inferior prognosis, while IRF4 mutations have been associated with a favorable prognostic impact [12].…”
Section: Liquid Biopsies: a Comprehensive And Non-invasive Alternativ...mentioning
confidence: 99%
“…Although still far from clinical practice, circulating biomarkers could assess patient eligibility for these targeted treatments. More data relate to the way in which mutation profiling can be used to detect and predict therapy resistance [15,36,37]. Coffey et al (2021) recently performed the targeted sequencing of cfDNA in 16 patients with RRMM and linked these results to highthroughput screening of drug compounds to predict response to these treatments.…”
Section: Towards Personalized Treatment In Multiple Myeloma Using Liq...mentioning
confidence: 99%
See 1 more Smart Citation
“…The RAS/MAPK pathway plays a crucial role in MM by influencing cell proliferation, survival, and differentiation. The activation of this pathway in MM is often driven by mutations and increased levels of cytokines present in the tumor microenvironment, such as IL-6, insulin-like growth factor (IGF), and vascular endothelial growth factor (VEGF) [ 84 86 ]. The aberrant activation of RAS/MAPK pathway contributes to the development and progression of MM and other cancers [ 87 , 88 ].…”
Section: Introductionmentioning
confidence: 99%